Caring for Old Age Perspectives from South Asia - Brosius, Christiane; Mandoki, Roberta (Heidelberg Studies on Transculturality, 2020)
Many societies are experiencing growing longevity and population ageing simultaneously with increasing urbanization and mobilities. Such fundamental demographic and structural shifts have been reflected in a multitude of narratives and strategies how to "age well" in view of rapidly transforming environments, mobilities of people and changing social relations. This volume explores the transcultural dimensions of ageing and care through close-up ethnographic and literary case studies in South Asia, as well as one European case study from a South Asian researcher's view. By critically engaging with Eurocentric aspects in ageing studies, the eleven contributions of this volume highlight how perspectives from the Global South shed light on transcultural entanglements and connectivities of experiences of care and ageing.